Delayed Haematological recovery after autologous stem cell transplantation is associated with favourable outcome in acute myeloid leukaemia. (12th September 2014) - Wetzel, Dana; Mueller, Beatrice U.; Mansouri Taleghani, Behrouz; Baerlocher, Gabriela M.; Seipel, Katja; Leibundgut, Kurt; Pabst, Thomas
Summary Autologous stem cell transplantation (ASCT) is applied to consolidate first remission in patients with acute myeloid leukaemia (AML). However, outcome after ASCT widely varies among AML patients. We analyzed the prognostic significance of haematological recovery for neutrophils [absolute neutrophil count (ANC) >1·0 × 109/l] and platelets (platelet count >20·0 × 109/l), stratifying at day 20 after ASCT in 88 consecutive and homogeneously treated AML patients in first remission. We observed that patients with delayed recovery had better overall survival (OS; ANC: P < 0·0001 and platelets: P = 0·0062) and time to progression (TTP; ANC: P = 0·0003 and platelets: P = 0·0125). Delayed recovery was an independent marker for better OS and TTP in a multivariate analysis including age, gender, number of transfused CD34+ cells, cytogenetics, FLT3‐internal tandem duplication and NPM1 mutation. Our results suggest that delayed neutrophil and platelet recovery is associated with longer OS and TTP in AML patients consolidated with ASCT in first remission.